Mecanismos para la exportación del sombrero de cardulovica palmata hacia el mercado del sur de California-Estados Unidos - Carcamo Cervantes, Karem Mayvete (2014)
The development of this research paper entitled "MECHANISM FOR EXPORT PALMATA CARDULOVICA HAT TO THE MARKET OF UNITED STATES SOUTHERN CALIFORNIA " is a response to the problem that has been showing up in recent years in the Ecuadorian trade balance, this action presented negative balances because the number of imports is greater than that of exports, and therefore it is possible to show a low level of competitiveness compared to other countries in the region. In this context, the export of fine Toquilla Straw Hats, also aims to provide support to small-scale producers, who lack the expertise to export their product to international markets, and contribute not only to improving of the economy, but also seeks to promote socio-economic growth of these artisans, to improve their quality of life and be within the guidelines of Good Living. Therefore, the purposes of this study we have chosen the “Pile" Community of canton Montecristi in the Province of Manabí to treat their situation and analyze the economic feasibility of carrying out a project to export their product to the market of United States Southern California……